Trust the Patient Not the Doctor: The Determinants of Quality of Life in Cervical Dystonia - Ndukwe, Ihedinachi; O'Riordan, Sean; Walsh, Cathal B.; Hutchinson, Michael (Frontiers in Neurology, 2020)
Background: Mood disorder is common in cervical dystonia and can impact on quality of life. It often precedes the onset of cervical dystonia and does not improve with botulinum toxin therapy. Objective: To assess health-related quality of life in relation to mood disorder and measures of severity, disability and pain, in cervical dystonia patients receiving botulinum toxin therapy. Methods: In a single-center, University Hospital movement disorders clinic, we conducted a comprehensive, cross-sectional study of disease severity, non-motor symptoms, mood and health-related quality of life in patients with cervical dystonia receiving botulinum toxin therapy using TWSTRS-2 for pain, severity and disability; Beck Anxiety Inventory and Beck Depression Inventory. We assessed all variables in relation to health-related quality of life assessed by Cervical Dystonia Impact Profile-58 and the Euro-QoL Utility Index. Results: In 201 patients (136 women), mean age 61.5 years, significant determinants of impaired health related quality of life were: being a woman, reporting a history of anxiety or depression, prevalent pain, disability, anxiety and/or depression but not physician-assessed disease severity. Conclusion: Patient-reported measures of pain, disability and, most markedly, mood disorder, are significant factors affecting quality of life; these were totally unrelated to the neurologist-rated measure of disease severity. Mood disorders, the predominant predictor of quality of life, were not addressed in the botulinum toxin clinic.